1992
DOI: 10.1182/blood.v79.8.2107.bloodjournal7982107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-jun causes reversible proliferative arrest and withdrawal from the cell cycle

Abstract: We studied the effect of c-jun depletion in Friend murine erythroleukemia (F-MEL) cells stably transfected with a plasmid that allowed for the glucocorticoid-mediated conditional expression of c-jun antisense sequences. The c-jun cDNA used for the construction of the vector was modified so as to prevent the nonspecific targeting of junB and junD transcripts. High level and rapid induction of c-jun antisense transcripts was achieved with as little as 10(-8) mol/L dexamethasone (DEX) and resulted in a 80% to 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…JNK catalyzes the conversion of c-Jun to p-c-Jun, which enables AP-1 to increase the affinity to CREBBP and the transcription activity [34][35][36]. Concretely, it has been shown that phosphorylation of c-Jun at serine 63/73 residues is required for transcriptional activation of cyclin D1 [37]. This is supported by our finding that JNK inhibitor treatment resulted in the downregulation of cyclin D1 expression.…”
Section: Discussionsupporting
confidence: 72%
“…JNK catalyzes the conversion of c-Jun to p-c-Jun, which enables AP-1 to increase the affinity to CREBBP and the transcription activity [34][35][36]. Concretely, it has been shown that phosphorylation of c-Jun at serine 63/73 residues is required for transcriptional activation of cyclin D1 [37]. This is supported by our finding that JNK inhibitor treatment resulted in the downregulation of cyclin D1 expression.…”
Section: Discussionsupporting
confidence: 72%
“…More than that, the cell contains large concentrations of macromolecules (up to 400 g/L), among which are proteins, nucleic acids, lipids, glycans, and solvated ions [ 118 ], which suggests that approximately 40% of the cell volume can be occupied by macromolecules and become physically inaccessible to other molecules. Accordingly, it can be assumed that crowding conditions affect both the kinetics and thermodynamics of interactions between macromolecules, including protein folding and aggregation [ 119 , 120 , 121 ]. Since crowding has a strong effect on protein–protein interactions, its influence on the conformation and self-association of chaperones, interaction of chaperones with target proteins, and the aggregation of the target proteins should also be taken into account [ 122 ].…”
Section: Mechanisms Of the Formation Of Misfolded Proteinsmentioning
confidence: 99%